Coordinating Effort under Team‐Based and Individual Incentives: An Experimental Analysis* - RANKIN, FREDERICK W. (Contemporary Accounting Research, 2004)
Abstract This paper explores the behavior of workers in an environment where it is efficient to engage in the mutual exchange of help. Experimental data show that output and workers' payoffs are greater under team‐based incentives than under individual incentives in an environment where coordination is difficult. However, when the environment is more conducive to coordination (that is, a setting where agents interact repeatedly), output and payoffs are greater under individual incentives. Manipulation of the amount of mutually observable information provides evidence that team‐based incentives, relative to individual incentives, create a more difficult coordination problem for workers and that cooperation requires a richer informational environment.